ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KESEJAHTERAAN LANSIA DI KECAMATAN KARANGASEM - Bahari, I Gede Leo; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Bali is fourth largest province the most elderly population, at 10.75 percent of total population. This study to analyze simultaneous and partial influence of education level, employment status, residence, level of religiosity, and family support for the welfare of the elderly in Karangasem District, analyze family support moderate the influence of the level of religiosity on welfare of elderly in Karangasem District, and determine the dominant factors that the most influential on the welfare of the elderly. The samples 122 elderly residents in Subagan Village and Karangasem Village with accidental sampling method. Analysis technique used moderated regression analysis. The results the study are 1) The level of education, employment status, residence, and level of religiosity simultaneously affect the welfare of the elderly in Karangasem District. 2) The level of education, employment status and residence partially have a positive effect on the welfare of the elderly in Karangasem District. 3) The interaction of family support with the level of religiosity towards the welfare of the elderly, including the type of pure moderation. 4) The dominant variable influencing the welfare of the elderly is the family support variable.   Keywords: elderly, education level, employment status, residence, level of religiosity, family support, elderly welfare.